WIZERUNEK ROSJI W ROSYJSKICH MEDIACH W ŚWIETLE KRYZYSU UKRAIŃSKIEGO - Jaskólski, Adam (Przegląd Rusycystyczny, 2017)
The main goal of this paper is to analyze utterances that were published by the Russian website “Odnako.org” in the period from March 1st of 2014 to May 15th of 2016. These utterances are concerned with the Ukrainian crisis. The starting point for the analisys is the opposition “We–They”. The existence of this opposition determines the necessity to characterize one’s own camp positively and to describe the opponent negatively. The author attempts to depict the image of Russia created in its mass media during the Ukrainian crisis. The author proposes a structural description of linguistic expressions as well as a determination of the rules of their functioning in analyzed utterances. The analysed linguistic expressions were grouped according to their belongingness to a specific semantic field or their systemic function. Attention was devoted to the linguistic expressions which name properties ascribed to Russia